Perbandingan Perilaku Seismik Struktur High-Rise Beton Bertulang dengan Penerapan Base Isolator LRB dan FPS - Wahyu Pamungkas, Hegar; Rochmah, Nurul (Universitas Iskandar Muda, 2025)
Banda Aceh is located in a region with high seismic activity due to the interaction between the Indo-Australian and Eurasian plates, making high-rise buildings in this area require a reliable earthquake-resistant structural design. This study aims to analyze and compare the dynamic behavior of reinforced concrete structures using Lead Rubber Bearing (LRB) and Friction Pendulum System (FPS) base isolation systems against the conventional fixed-base system. The modeling was carried out on a 10-story apartment building using ETABS v.17, referring to SNI 1726:2019, SNI 1727:2020, and SNI 2847:2019 standards. The analysis results show that the base isolation systems reduce inter-story drift by up to 77% for FPS and 49% for LRB compared to the fixed-base model, but increase the total structural displacement with maximum values reaching 2254% for LRB and 1889% for FPS due to isolator movement. Furthermore, the base shear force increased approximately 3.16 times for LRB and 3.40 times for FPS compared to the fixed-base system. The use of isolation also significantly extends the structural vibration period, with the largest increase in the first mode reaching 77% for LRB and 67% for FPS. Overall, the implementation of base isolation effectively enhances structural flexibility and seismic response while reducing potential structural and non-structural damage in earthquake-prone regions.